Bacterial cellulose production by Gluconacetobacter xylinus by employing alternative culture media - Jozala, Angela Faustino (2015)
Bacterial cellulose (BC) is used in different fields as a biological material due to its unique properties. Despite there being many BC applications, there still remain many problems associated with bioprocess technology, such as increasing productivity and decreasing production cost. New technologies that use waste from the food industry as raw materials for culture media promote economic advantages because they reduce environmental pollution and stimulate new research for science sustainability. For this reason, BC production requires optimized conditions to increase its application. The main objective of this study was to evaluate BC production by Gluconacetobacter xylinus using industry waste, namely, rotten fruits and milk whey, as culture media. Furthermore, the structure of BC produced at different conditions was also determined. The culture media employed in this study were composed of rotten fruit collected from the disposal of free markets, milk whey from a local industrial disposal, and their combination, and Hestrin and Schramm media was used as standard culture media. Although all culture media studied produced BC, the highest BC yield60 mg/mLwas achieved with the rotten fruit culture. Thus, the results showed that rotten fruit can be used for BC production. This culture media can be considered as a profitable alternative to generate high-value products. In addition, it combines environmental concern with sustainable processes that can promote also the reduction of production cost.